IL-6 trans-signaling in cystic fibrosis bronchial cells potentiates TNF-α-driven ICAM-1 expression - Lin, John; Fourcade, Lyvia; Roussel, Lucie; Marabella, Matthew; Bérubé, Julie; Nguyen, Dao; Rousseau, Simon (Frontiers in Cell and Developmental Biology, 2025)
IntroductionPseudomonas aeruginosa is gram-negative bacillus that causes chronic airway infections, leading to severe pulmonary inflammation in cystic fibrosis. This bacterial infection is frequently associated with a massive recruitment of neutrophils and an abnormal increase in production of inflammatory cytokines. Among these cytokines, interleukin (IL)-6 has both anti- and pro-inflammatory properties able to signal through classic and trans-signaling pathways, respectively. Furthermore, IL-6 is known to be upregulated in CFTR-deficient bronchial cell lines in the presence of Pseudomonas aeruginosa-derived filtrates and in Pulmonary Exacerbations (PEx). In this study, we aimed to determine whether IL-6 trans-signaling could contribute to neutrophilic inflammation leading to lung tissue damage during PEx of people with CF (pwCF).MethodssIL-6Ra expression was measured by ELISA in plasma samples from pwCF at baseline and during exacerbations. IL-6 signalling was investigate in CF and non-CF cell lines using immunoblotting of STAT3 phosphorylation. ICAM-1 cell surface expression was determined using flow cytometry.ResultsWe show that pwCF had higher sIL-6Rα levels in their plasma during PEx, suggestive of IL-6 trans-signaling. Furthermore, we show that a CF bronchial cell line is hyper-responsive to both classic and trans-signaling, with the higher levels of activation occurring during trans-signaling when compared to two non-CF cell lines.DiscussionOur data unveiled that ICAM-1, which promotes neutrophil adhesion, is upregulated by the combination of TNF-α and IL-6 signaling in CF bronchial cells. Interestingly, soluble IL-6R (sIL-6Rα) protects IL-6 from degradation by bacterial proteases. Therefore, we suggest that strategies which target IL-6 trans-signaling may alleviate ICAM-1 mediated neutrophil adhesion and reduce subsequent lung damage in PEx.